Peran Badan Usaha Milik Desa(BUMDes) dalam Pemberdayaan Masyarakat Desa Kedungwonokerto Kecamatan Prambon Kabupaten Sidoarjo - Fatzrin, Dea; Prathama, Ananta (Jurnal Pemerintahan dan Politik, 2024)
Indonesia as a country with a population spread across various islands certainly has differences in each region or region. Prosperity that is built in every region or region in Indonesia can enable people to have a decent standard of living. Welfare and empowerment are interconnected in society. Community empowerment in villages also needs to be carried out continuously so that the local economy can compete in the current era of globalization. This is the basis for this research. The aim of this research is to determine the role of BUMDes in empowering the community of Kedungwonokerto Village, Prmain District, Sidoarjo Regency. The village government forming BUMDes is one step in reviving the local village economy. The role of BUMDes in community empowerment can be seen as the first step in helping to improve the local village economy. The village government together with BUMDes contribute by becoming a forum for existing and newly started business actors so that they can continue to grow and develop. This research uses qualitative research based on the results of observations, interviews and documentation. The results of this research are that BUMDes provides efforts to empower the community through training and outreach activities, creating a website to sell products online, establishing a special place for village communities to sell or culinary as well as bazaar activities aimed at introducing village community business products.